IL‐33 and IgE stimulate mast cell production of IL‐2 and regulatory T cell expansion in allergic dermatitis. Issue 11 (26th September 2017) - Salamon, P.; Shefler, I.; Moshkovits, I.; Munitz, A.; Horwitz Klotzman, D.; Mekori, Y. A.; Hershko, A. Y.
Summary: Background: We have previously shown that mast cells (MCs) suppress chronic allergic dermatitis in mice. The underlying mechanism involves MC‐derived IL‐2, which supports regulatory T cell (Treg) response at the site of inflammation. However, it is not clear what are the factors that drive MCs to produce IL‐2. Objective: To understand the mechanisms that lead to IL‐2 production from MCs in chronic allergic dermatitis. Methods: Isolated murine bone marrow‐derived MCs (BMMCs) were incubated with various stimulators, and IL‐2 production was assessed by RT‐PCR and ELISA. The response of signalling pathways was evaluated by MAPK inhibitors and Western blot analysis. The effect of MC‐IL‐2 on Tregs was studied by incubation of splenic T cells with conditioned media obtained from activated BMMCs. Dermatitis was elicited by repeated exposures of mouse ears to oxazolone. MCs in mouse and human skin samples were evaluated by immunostaining. Results: BMMCs released IL‐2 in response to IL‐33, and IL‐2 production was further enhanced by concomitant FcεRI activation. The effect of IL‐33 was mediated by activation of the MAPK family members. IL‐2 in conditioned media from IL‐33 and IgE‐stimulated BMMCs led to considerable expansion of Tregs in vitro. IL‐33 levels were elevated in oxazolone‐challenged ears along with increased numbers of IL‐2‐expressing MCs. Human skin with chronic inflammation also contained IL‐2‐expressing MCs that colocalized with IL‐33 staining in the dermis. Conclusions: IL‐33, in collaboration with IgE, is critical for MC‐IL‐2 production in allergic skin disease, thus leading to Treg stimulation and suppression of allergic dermatitis.